SOSIALISASI DAN EDUKASI ANALISIS KELAYAKAN DAYA TARIK WISATA DI DESA KALIKIDANG, JAWA TENGAH - Liliana Dewi; Rizki Nurul Nugraha; Rachmad Rizky Trianto (JURNAL PENGABDIAN MANDIRI, 2023)
Kalikidang village, Banyumas regency, Central Java has fisheries potential as well as scenery such as hills that can be utilized as a tourist destination. However, based on the findings of interviews and observations with the community, it is clear that the potential is still in the form of embryos, with management unsure how to manage the potential until it becomes a tourist destination. In order to help increase the communities capabilities, the team provided socialization and education on how to assess the feasibility of a location or area as a possible and sustainable tourist destination. The process is carried out by directly observing and analyzing the potential in the field. Followed by a shared discussion of the outcomes of the field observations. As a result of participation in a series of events, the community has a better understanding of how to manage a potential tourist attraction that needs to see and evaluate the implications that have a long-term nature of the growth of a tourist attraction.